Dynamometric and kinemetric analyses of take-off in ski jumping - Kurz, O.; Mornieux, G.; Golihofer, A. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: The quality of the take-off phase in ski jumping is influenced by many different parameters. Both dynamometric and kinemetric measurements have been done for many years. In the present study both methods were combined to obtain an integrated assessment of Jumpers with different performance levels.